Bone Regeneration Potential of Uncalcined and Unsintered Hydroxyapatite/Poly l-lactide Bioactive/Osteoconductive Sheet Used for Maxillofacial Reconstructive Surgery: An In Vivo Study - Dong, Quang Ngoc (Materials (Basel), 2019)
Uncalcined and unsintered hydroxyapatite/poly l-lactide (u-HA/PLLA) material has osteoconductive characteristics and is available for use as a maxillofacial osteosynthetic reconstruction device. However, its bone regeneration ability in the maxillofacial region has not been fully investigated. This study is the first to assess the bone regenerative potential of osteoconductive u-HA/PLLA material when it is used for repairing maxillofacial bone defects. A total of 21 Sprague-Dawley male rats were divided into three groups—the u-HA/PLLA, PLLA, or sham control groups. A critical size defect of 4 mm was created in the mandible of each rat. Then, the defect was covered with either a u-HA/PLLA or PLLA sheet on the buccal side. The rats in each group were sacrificed at 2, 4, or 8 weeks. The rats’ mandibles were sampled for histological analysis with hematoxylin and eosin staining, histomorphometry, and immunohistochemistry with Runx2 and osteocalcin (OCN) antibody. The amount of newly formed bone in the u-HA/PLLA group was significantly higher than that of the PLLA group. The expression of Runx2 and OCN in the u-HA/PLLA group was also significantly higher. These results demonstrate that the u-HA/PLLA material has excellent bone regenerative ability and confirm its applicability as a reconstructive device in maxillofacial surgery.